PENGARUH KEPERCAYAAN MEREK DAN KESAN KUALITAS TERHADAP KEPUTUSAN PEMBELIAN ULANG - KUSUMA A, AGMERTYA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract :This research aims to analyze and find out the influence of brand trust and perceived quality on anlene repurchases decision. The population in this study is men are wowen earning at least 19 years old and involved in the anlene repurchase decision. Sample taken as many as 110 people with proposive sampling techique. The measutring used was questionare, and data were analyzed by multiple linier regresions. The result showed that there were significant influence of brand trust and perceived quality to Anlene repurchases decisions. The value of coeffcient determination (Adjusted R2) showed that the brand trust and perceived quality have an influence of anlene repurchases decision. From regression coefficient showed that brand trust has dominant in influincing repurchases decision. Keywords : brand awareness, brand associations, perceived quality, brand loyalty, and purchase decisions.